Pengaruh Kursus Keterampilan Hidup (Life Skills) terhadap Ketahanan Psikososial Siswa Sekolah Dasar - Rahmawati, Siti; Pratama, Andi; Aisyah, Nur (Gema Cendekia Institute, 2026)
Psychosocial resilience among elementary school students is a crucial aspect in facing developmental challenges and environmental stressors. Life skills courses have been identified as potential preventive interventions to enhance children's adaptive capacities. This study aims to analyze the effect of life skills courses on the psychosocial resilience of elementary school students in Indonesia. A quasi-experimental study with a pretest-posttest control group design involved 120 fourth and fifth-grade elementary students in Bandung. The experimental group (n=60) received a 12-week life skills course intervention, while the control group (n=60) followed regular instruction. Measurement instruments included the Child and Youth Resilience Measure (CYRM-28) and Life Skills Assessment Scale. Data were analyzed using ANCOVA and paired sample t-tests. Results showed a significant increase in psychosocial resilience in the experimental group (M=78.45, SD=8.32) compared to the control group (M=65.21, SD=7.89), F(1,117)=68.34, p<0.001, η²=0.37. Social skills, problem-solving, and emotional regulation dimensions demonstrated the most substantial improvements. Life skills courses proved effective in enhancing elementary school students' psychosocial resilience with a large effect size, indicating potential implementation as a universal prevention program in Indonesian schools.